Contraceptive Selection among Couples of Childbearing Age in the Perspective of Healthcare Workers - Riska Dwi Prihatiningsih; I Wayan Agung Indrawan; Nanik Setijowati (Babali Nursing Research, 2024)
Background: Women are susceptible to unwanted pregnancies. This makes them susceptible to risk factors such as maternal mortality, abortion, and stress. This study aims to explore health workers' perspectives on contraceptive selection among couples of childbearing in East Lombok Regency.